2023
DOI: 10.1186/s12870-022-04028-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism analysis of the chloroplast and mitochondrial genomes in soybean

Abstract: Background Soybean is an important protein- and oil-rich crop throughout the world. Much attention has been paid to its nuclear genome, which is bi-parentally inherited and associated with many important agronomical traits. However, less is known about the genomes of the semi-autonomous and essential organelles, chloroplasts and mitochondria, of soybean. Results Here, through analyzing the polymorphisms of these organelles in 2580 soybean accession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…and mt genomes in the date palm was confirmed by the same analysis performed with another published date palm dataset [ 3 ]. A difference of the same magnitude, although of opposite direction, was observed in soybean [ 45 ] and Ginkgo [ 46 ] where Ts/Tv were 0.99 and 2.29 in mtDNA and 0.2 and 0.61 in cpDNA, respectively. It has already been reported that the rate of transversions can be slightly higher than that of transitions in the date palm mitochondrial genome [ 18 ].…”
Section: Discussionmentioning
confidence: 68%
“…and mt genomes in the date palm was confirmed by the same analysis performed with another published date palm dataset [ 3 ]. A difference of the same magnitude, although of opposite direction, was observed in soybean [ 45 ] and Ginkgo [ 46 ] where Ts/Tv were 0.99 and 2.29 in mtDNA and 0.2 and 0.61 in cpDNA, respectively. It has already been reported that the rate of transversions can be slightly higher than that of transitions in the date palm mitochondrial genome [ 18 ].…”
Section: Discussionmentioning
confidence: 68%
“…This study analyzed the chloroplast genomes of 104 P. montana accessions, identifying 1118 SNPs and 556 indel variations with high intraspecies variability ( Table 1 ). P. montana chloroplast genome showed higher variability compared with other published plant species, such as Ginkgo biloba (135 SNPs, 71 accessions) [ 52 ], Brachypodium distachyon (298 SNPs, 53 accessions) [ 51 ], soybean (44 SNPs, 2580 accessions) [ 53 ], Coptis chinensis (111 SNPs, 227 accessions) [ 19 ], and Ulmus laevis (32 SNPs, 54 accessions). Mutation heterogeneity across different plant lineages or species has been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of polymorphisms in 2580 soybean accessions, including 107 wild soybeans, revealed that the chloroplast genome is more variable than the mitochondrial genome in terms of variant density [ 70 ]. Cultivated soybeans harbored 44 chloroplast haplotypes and 30 mitochondrial haplotypes, with the two most frequent types accounting for nearly 70 and 18%, respectively [ 70 ]. Wild soybeans, on the other hand, had 32 chloroplast and 19 mitochondrial haplotypes.…”
Section: Cytoplasmic Inheritancementioning
confidence: 99%
“…However, only a small proportion of cultivated soybeans shared cytoplasm with wild soybeans. Two mitochondrial polymorphism sites were discovered to be heterozygous in most soybeans, suggesting a link between heterozygosity and domestication, improvement of landraces, geographic adaptation [ 70 ]. The haplotypes of many soybean cultivars could be beneficial for evaluating the impact of cytoplasm on performance, as well as for breeding cultivars with desired cytoplasm.…”
Section: Cytoplasmic Inheritancementioning
confidence: 99%
See 1 more Smart Citation